Effect of external store on a generic subsonic fighter aircraft - Hoq, K.M. Tafsirul; Talal, Abdelrahman; Mat, Shabudin; Ramli, Yahaya (The Aeronautical and Astronautical Society of the Republic of China, 2024)
In contemporary military and transport aircraft, wing-mounted external storage is commonly used when there is insufficient space within the fuselage. The installation of these external stores can significantly alter the flow around adjacent components, causing a change in aerodynamic characteristics. The objectives of this research are to investigate the effects of different locations of external stores and the effects of flaperon deflection on the aerodynamic characteristics and stability of a generic subsonic fighter aircraft. The study involves examining six different configurations of external stores mounted under the wing, and for the flaperon, four deflection angles were chosen with the aim of measuring the aerodynamic forces and moments. These experiments were carried out at wind speeds of 30 m/s corresponding to Reynolds numbers of 0.6 × 106 for angles of attack ranging from -2° to 24°. The analysis revealed that the presence of external stores positioned at both the tip chord and 38 cm from the root chord significantly increased the lift coefficient to a value of 1.09 compared to other configurations. The introduction of flaperon deflection also led to increased drag at higher angles of attack and demonstrated its maximum efficiency at an angle of attack (α) of 10 to 12 degrees.